Charge-based interactions between peptides observed as the dominant force for association in aqueous solution. - McLain, SE; Soper, A; Daidone, I; Smith, J; Watts, A (2008)
What's the attraction? The structures of three dipeptides in aqueous solutions were investigatedby using a combination of neutron diffraction and computer simulation. In each solution, peptide association was dominated by charge-charge rather than hydrophobic interactions (see the representative snapshot of the peptide/water box for glycyl-L-alanine; the water molecules are depicted by red crosses.) (Figure Presented) © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.